Developing an English for Presentation Textbook to Support Speaking Skills in General English Course - Adelia Puspa; Anggun Citra Sari Dewi; Perti Rosanda (International Journal of Innovation and Education Research, 2026)
The ability to deliver effective presentations in English has become an essential competency for university students. However, many students enrolled in the General English course still experience difficulties in organizing presentations, using appropriate presentation expressions, and delivering ideas confidently. In addition, instructional materials specifically designed to support English presentation skills in General English contexts remain limited. This study aimed to develop and validate an English for Presentation textbook to support students' speaking skills in General English courses at the University of Bengkulu. The study employed a Research and Development (R&D) design adapted from Borg and Gall, involving needs analysis, product development, expert validation, field testing, and product revision. Data were collected through classroom observations, interviews, focus group discussions, and questionnaires administered to expert validators and students. Qualitative data were analyzed using an interactive analysis model, while quantitative data were analyzed descriptively using percentages. The findings revealed that the developed textbook successfully addressed students' learning needs by integrating presentation language, presentation strategies, and practical speaking activities into a structured learning resource. Expert validation indicated that the textbook was valid in terms of content, presentation, and language, while the field trial showed that more than 90% of students responded positively to its clarity, relevance, and usability. These findings suggest that the textbook is both valid and practical for use in General English courses and may serve as an alternative instructional resource to support the development of students' English presentation skills in higher education. Keywords: English for Presentation, Instructional Material Development, General English, Presentation Skills, Research and Development